Prioritizing issues of Malaysian Vision 2020: an application of the analytic hierarchy process and quality function deployment - Islam, Rafikul; Ismail, Yusof (International Islamic University Malaysia, 2011)
The objectives of this research are to obtain the people’s perception towards a number of issues pertaining to the realization of Malaysian Vision 2020, to rank the challenges of Vision 2020 and to collect suggestions to expedite the realization of the vision. Based on a nationwide survey, an affinity diagram was formed and the Analytic Hierarchy Process (AHP) was applied to identify the main issues for implementation. Furthermore, the Quality Function Deployment (QFD) model was utilized to show the strength of relationships between the various challenges of Vision 2020 and twenty categories of suggestions obtained in the survey. The respondents were also asked to rank the nine strategic challenges of Vision 2020, and the results show the three most crucial Vision 2020 challenges: ‘Establishing a fully moral and ethical society’, ‘Establishing a united Malaysian nation made up of one Bangsa Malaysia (Malaysian nation)’, and ‘Creating a psychologically liberated, secure and developed Malaysian society’. The AHP prioritization process also identifies the salient public suggestions. The findings suggest that the government machinery should keep the public better informed of the issues, improve their perceptions and solicit their contributions. Since this study focuses on urban respondents with higher educational qualifications, future studies should focus on those in rural areas. As the government needs to be aware of the public feedback on the issue, this survey has managed to identify what are lacking in the government’s efforts and what more need to be done in order to expedite the realization of Vision 2020.